PENGARUH AKTIVITAS FISIK (JALAN KAKI) TERHADAP KADAR GULA DARAH PENDERITA DIABETES MELITUS TIPE 2 USIA PRODUKTIF DI PUSKESMAS KESAMBEN KULON - Kartiningrum, Eka Diah; Vettaria Sulita Utama; Anndy Prastya (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Diabetes mellitus is a metabolic disease caused by the increasing level of glucose in the blood, this happens as an impact of a disorder either in insulin secretion or insulin performance, or both. Walking as a physical activity played an important role in blood sugar level control and reducing urine resistance towards sugar for type 2 diabetes mellitus patients at productive age. The purpose of this study is to determine the impact of walking as physical activity on the blood sugar level of type 2 diabetes mellitus patients at productive age. The research used quasi- experimental design, one group pretest-posttest type, with Isaac and Michael formula for sampling technique. The total sample was 33 people. This reseach was conducted in March 2021. The result of this research showed that the average blood sugar level of the patients before walking treatment was 224,79mg/dl, and theiraverage blood sugar level after the treatment dropped to 165,42mg/dl. This study used a t – test significance level of 5%, and the result showed that t-count was 66.654 greather than t -table which was 1,69092, therefore the value of significance was less than 0,05. It means that there was an impact of walking on blood sugar level of type 2 diabetes mellitus patients at productive age in Kesamben Kulon Health Center. The conclusion was that walking activity can be used to reduce blood sugar level of type 2 diabetes mellitus patients at productive age.